Platform ad archives: promises and pitfalls - Paddy Leerssen; Jef Ausloos; Brahim Zarouali; Natali Helberger; Claes H. de Vreese (Internet Policy Review, 2019)
This paper discusses the new phenomenon of platform ad archives. Over the past year, leading social media platforms have installed publicly accessible databases documenting their political advertisements, and several countries have moved to regulate them. If designed and implemented properly, ad archives can correct for structural informational asymmetries in the online advertising industry, and thereby improve accountability through litigation and through publicity. However, present implementations leave much to be desired. We discuss key criticisms, suggest several improvements and identify areas for future research and debate.
Keywords: 300; Advertising; Micro-targeting; Platforms; Transparency; Politics